Regulation of aggrecanases from the ADAMTS family and aggrecan neoepitope formation during in vitro chondrogenesis of human mesenchymal stem cells - Boeuf, Stephane; Moradi, Babak; Richter, Wiltrud (European cells & materials, 2012)
Aggrecanases from the ADAMTS (A Disintegrin And Metalloproteinase with ThromboSpondin motifs) family are important therapeutic targets due to their essential role in aggrecan depletion in arthritic diseases. Whether their function is also important for matrix rearrangements during chondrogenesis and thus, cartilage regeneration, is however so far unknown. The aim of this study was to analyse the expression and function of ADAMTS with aggrecanase activity during chondrogenic differentiation of human mesenchymal stem cells (MSCs). Chondrogenic differentiation was induced in bone marrow-derived MSC pellets and expression of COL2A1, aggrecan, ADAMTS1, 4, 5, 9, 16 and furin was followed by quantitative RT-PCR. Formation of the NITEGE (ADAMTS-cleaved) and DIPEN (MMP-cleaved) aggrecan neoepitopes was detected by immunohistochemistry. While the expression of ADAMTS4, 9, 16 and furin was up-regulated during chondrogenesis, ADAMTS1 and 5 were down-regulated. Despite this regulation of ADAMTS, no formation of NITEGE neoepitopes occurred in MSC pellets, indicating no ADAMTS-induced cleavage of aggrecan. In contrast, MMP-induced cleavage of aggrecan appeared at 14 d after induction of chondrogenesis. Submission of differentiated MSC pellets to IL1β treatment for 3 d resulted in strong upregulation of ADAMTS1, 4 and 5, rapid proteoglycan depletion, and stimulation of ADAMTS-induced but not MMP-induced cleavage of aggrecan. Thus, there is no evidence for ADAMTS-induced aggrecan cleavage during chondrogenesis, but proteoglycan turnover is rapidly inducible under inflammatory signals. Therapeutic aggrecanase inhibition for treatment of arthritic disease may thus not impede regenerative self-healing pathways based on chondrogenesis of local progenitor cells in the joint.